Pengembangan Sistem Alumni dengan Informasi Lowongan Pekerjaan - Daniel Jahja Surjawan; Meliana Christianti Johan; Dinda Ayu Febriani (Maranatha University Press, 2022)
The Faculty of Information Technology, Maranatha Christian University or known as FIT-UK Maranatha has produced many alumni since its establishment in 2002. The recording of alumni data is currently not well managed where the data collected by the faculty is based on the latest information provided by alumni before final presentation or graduate briefing events. It is the hope of the faculty to have a special website-based application that can accommodate alumni data so that the faculty can still communicate with alumni and fellow alumni, while also getting the latest information related to current industry needs. This research will create a web-based application where the application can record alumni data, friendships between alumni, record the data of open job vacancies at the company where alumni work that can be seen by other alumni. The website will be made using the PHP programming language and the Laravel framework, for data storage will use mySQL.